2009
DOI: 10.1002/pola.23351
|View full text |Cite
|
Sign up to set email alerts
|

Green polymer chemistry using nature's catalysts, enzymes

Abstract: ABSTRACT:The use of enzymes as catalysts for organic synthesis has become an increasingly attractive alternative to conventional chemical catalysis. Enzymes offer several advantages including high selectivity, ability to operate under mild conditions, catalyst recyclability, and biocompatibility. Although there are many examples in the literature involving enzymes for the synthesis of polymers, our search showed that very little had been done in the area of polymer modification. In this article, we will discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 73 publications
1
84
0
1
Order By: Relevance
“…124 Como outro exemplo desta área, tem-se a funcionalização de PEG comercial pela sua transesterificação com vinil ésteres, catalisada por uma lipase, resultando em polímeros PEG-acrilatos. 125 …”
Section: Funcionalização De Poli(etilenoglicol)unclassified
“…124 Como outro exemplo desta área, tem-se a funcionalização de PEG comercial pela sua transesterificação com vinil ésteres, catalisada por uma lipase, resultando em polímeros PEG-acrilatos. 125 …”
Section: Funcionalização De Poli(etilenoglicol)unclassified
“…Go green is one of the most recent trends in community of science and technology in the effort to promote sustainability in ensuring the future generation can enjoy what the world is like today. More and more studies have reported examples of adopting greener approach in their works, for instance in extraction [16], catalyst [17], polymer technology [18], and organic synthesis [19].…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of green polymer chemistry, green catalysts and polymer production methods are importantly noted [3][4][5][6][7][8][9]. Carbon-neutral material is a material which does not affect the change in carbon dioxide amount emitted and absorbed in the materials' cycle.…”
Section: Introductionmentioning
confidence: 99%